Philosophical and Psychological Analyze of Tolerance - Septian, Muhammad Rezza; Supriatna, Mamat; Nurihsan, Juntika; Budiman, Nandang (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
This article contains an analysis of the philosophical and psychological studies of tolerance in the context of guidance and counseling. The scope of the tolerance study includes a philosophical review and a psychological review of tolerance. The method used is the literature review method, with five stages, namely looking for similarities (compare), looking for dissimilarities (contrast), providing views (criticizing), comparing (synthesizing), and summarizing (summarizing). The results of the study show that philosophical tolerance is influenced by idealism and humanism and is supported by the philosophers Socrates, Spinoza, John Stuart Mill, Jurgen Habermas, Karl Popper, John Rawls, Michael Walzer and Neville. The psychological figures namely Andrew Murphy, Amy Guttmann, and Gordon Allport. The results of the analysis can also be used as material for research and development of tolerance programs in guidance and counseling services.